Minha hist??ria conto eu: escola e cultura prisional em institui????o carcer??ria no Amap?? - Neves, Edmar Souza das (2017)
The purpose of this study was to analyze the relationships established within the prison school between the different cultures that attend it: school culture and prison culture. It intends to verify if the way in which these relations are processed contributes or not to the process of social reintegration. In order to do so, he investigated the life history of the subjects deprived of their liberty in their relations with the prison and the prison school, based on the theoretical and methodological presuppositions of Oral History, using the Critical Discourse Analysis proposed by Kress (1990) as Analysis of the data produced. The study included two prisoners serving sentences in the closed regime who are regularly enrolled in prisons. The interviews were carried out inside the S??o Jos?? School, located in the penitentiary complex of Amap??, the research site of this study. The theoretical references that support our analysis start from the studies developed by Michel Foucault (1926-1984) and Erving Goffman (1922-1982). On the social phenomena that develop in the daily life of prisons and schools, in the critical studies of several researchers, Brazilian and foreign, on the reality of prisons and, particularly, the prisons school. We find that the daily prison life is composed of rules, moral codes, norms and values proper to intramural life, forming a true prison culture, and that these elements almost always function as blockers of the processes of resocialization, as in the manipulation of the concepts of " Masculine "and" feminine ", the presence of" homoeroticism "being a constituent element of prison culture. As for the prison school, we have identified that it takes the disciplinary rules of the jail as the north of its disciplinary actions; That the interpersonal relations established within it are based on reciprocal fear; That prison officers practice violence against students in custody; That the school is a manifestation of homophobia and exclusion and offers a teaching that is not different from the education offered by the school outside the walls; That the subjects interviewed believe in the importance that educational assistance exerts on their lives, even though they affirm that the pedagogical practices developed within the school do little to contribute to the process of social reintegration. It is concluded that daily prison, with its norms, rules, values, moral codes and customs, produces a culture typical of prisons which, in turn, defines specific relations with the prison school that tend not to operate in favor of the process Social reintegration of the prisoner. The aim of the work was to contribute to educators, public authorities and society to give new insights on prison life and the way in which educational assistance has been offered to prisoners deprived of their freedom and has assisted in social reintegration.